Attention to the worker's health care: a tool to subsidize nursing visits - Denise Cristina Alves de Moura; Paula Cristina Gomes; Gilvan Carlos Toledo Júnior; Nathália Alvarenga-Martins; Rosangela Maria Greco (Universidade Federal de Santa Maria, 2016)
Aim: to describe the development of forms for data collection, diagnoses, prescriptions and nursing outcomes to support the nursing process during occupational health care. Method: account experience of building a tool to systematize nursing care in consultation with the worker. Results: three health data collection tools were created : the first one intended to register nursing track record; the second lists 26 nursing diagnoses and the third describes 22 possible nursing interventions and 23 Nursing expected results. The last two were aligned according to North American Nursing Diagnosis Assosciation International (NANDA I), Nursing Intervention Classification International (NIC), Nursing Outcome Classification ( NOC) taxonomies. Conclusion: the contributions to nursing and to the worker health were: the creation of an instrument to subsidize the systematized nursing consultation to workers; compliance with current legislation on the implementation of the nursing process.